Cultural and health beliefs of pregnant women in Zambia regarding pregnancy and child birth - Namakau C. M'soka; Langalibalele H. Mabuza; Deidre Pretorius (AOSIS, 2015)
Background: Health beliefs related to pregnancy and childbirth exist in various cultures globally. Healthcare practitioners need to be aware of these beliefs so as to contextualise theirpractice in their communities. Objectives: To explore the health beliefs regarding pregnancy and childbirth of womenattending the antenatal clinic at Chawama Health Center in Lusaka Zambia. Method: This was a descriptive, cross-sectional survey of women attending antenatal care(n = 294) who were selected by systematic sampling. A researcher-administered questionnairewas used for data collection. Results: Results indicated that women attending antenatal care at Chawama Clinic held certain beliefs relating to diet, behaviour and the use of medicinal herbs during pregnancy and post-delivery. The main beliefs on diet related to a balanced diet, eating of eggs, okra, bones, offal, sugar cane, alcohol consumption and salt intake. The main beliefs on behaviour related to commencement of antenatal care, daily activities, quarrels, bad rituals, infidelity and the use of condoms during pregnancy. The main beliefs on the use of medicinal herbs were on their use to expedite the delivery process, to assist in difficult deliveries and for body cleansing following a miscarriage. Conclusion: Women attending antenatal care at the Chawama Clinic hold a number of beliefs regarding pregnancy and childbirth. Those beliefs that are of benefit to the patients should be encouraged with scientific explanations, whilst those posing a health risk should be discouraged respectfully.